An Evaluation of the Need and Cost of Selected Trade Facilitation Measures in China: Implications for the WTO Negotiations on Trade Facilitation - Li Wei Wenjing Chen (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2006)
In 2004, China became the third largest trading economy in the world. Although official overall average import tariff rate was reduced to 9.9% as of January 2005, actual tariff rates are likely much lower. Although further tariff reductions may lead to renewed and expanded global trade growth, trade facilitation will play an increasingly important role in promoting global trade. Costs associated with implementation of trade facilitation measures may be classified into four categories: new regulations, institutional changes, training, and equipment and infrastructure. The study was generally not able to determine costs of specific trade facilitation measures in China. However, Customs and the General Administration of Quality Supervision, Inspection and Quarantine (AQSIQ) are the two government departments that are most deeply involved in trade facilitation, and a review of their expenditures in this field provides useful information on equipment/infrastructure costs that may be associated with implementing modern trade facilitation systems.
Keywords: F1; 330; GATT; WTO; Trade Facilitation; China